Astaxanthin suppresses cigarette smoke and lipopolysaccharide-induced airway inflammation through induction of heme oxygenase-1 - Nian, Liu; Weidong, Zhang; Shujuan, Luo; Jun, Cao; Minlian, Peng; Zhiguang, Liu (Cellular and Molecular Biology, 2019)
The present study was carried out to evolve an effective treatment strategy for chronic obstructive pulmonary disease (COPD). Astaxanthin (AS) is abundantly present in red pigments of crustaceans, and has also been proven to have considerable biological activities. The anti-inflammatory effect of AS was evaluated in lipopolysaccharide (LPS)-exposed RAW264.7 macrophages. It was found that AS markedly inhibited elevation of NO and pro-inflammatory mediators. Moreover, it downregulated iNOS in LPS-stimulated RAW264.7 cells, suppressed the release of pro-inflammatory cytokines, and decreased ROS levels in mice exposed to cigarette smoke (CS) and LPS. These results imply that AS has therapeutic and prophylactic potential in the airway inflammatory response associated with COPD.